Preferential vs. Full Trade Liberalisation: A Dynamic CGE Model with Heterogeneous Households for Jordan - Omar Feraboli (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper deals with the economic effects and the policy implications of trade liberalisation on the Jordanian economy, with emphasis on welfare, income distribution and real wages of heterogeneous households, by using a neoclassical dynamic computable general equilibrium (CGE) model. Specifically the paper assesses the impacts of preferential trade liberalisation with the European Union (EU) and compare them with those brought about by broad and non-discriminatory trade liberalisation.
Keywords: C68; F11; I32; D31; 330; Dynamic CGE Models; Heterogeneous households; Trade liberalisation; Jordan